Memahami Tinjauan Hukum Islam dalam Investasi - Fathullah (Fakultas Syariah Institut Ilmu Keislaman Zainul Hasan, 2017)
Investments have a large share in the process of economic empowerment of a country. The existence of equity with the transfer of some shares produces results where there will be cooperation between individuals (shareholders and stock buyers) to create a division of labor and the elimination of unemployment that leads to poverty. The existing investment should be examined and examined more closely, especially when judging by Islamic law. Some of the elements involved in investments that are inconsistent with the Shari’ah should be eliminated and attempted more effective substitutes that can overshadow the interests of the masses, especially for Muslims.